TINJAUAN AKUNTABILITAS PENGELOLAAN KEUANGAN DESA DALAM PENERAPAN SISTEM INFORMASI AKUNTANSI DAN TUGAS POKOK DAN FUNGSI - Nainggolan, Edisah Putra; Sholeha, Dewi; Indriyani, Syahvira (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
The purpose of this study is to investigate and evaluate the impact of Main Duties and Functions and the Accounting Information System on the Accountability of Village Financial Management in the Villages of Sawit Seberang District Area, Langkat Regency. In this study, an associative technique was adopted. The six villages in the Sawit Seberang District of the Langkat Regency comprised the study's population. 42 participants from villages in the Sawit Seberang District of Langkat Regency made up the saturated sampling sample used in this study. In this study, questionnaires and observational methods were employed as data-gathering methods. This study's data analysis method is quantitative and employs statistical analysis, including hypothesis testing, Auter model analysis, and inner model analysis. Processing data for this study.